Demokrati og jødisk fundamentalisme i Israel - Paludan, Peter Steensgaard (Religionsvidenskabeligt tidsskrift, 2000)
This study - Jewish Fundamentalism in Israel and Democracy - examines the political concepts and practice of the haredi (ultra-orthodox) political parties, Shas and United Torah Judaism. It tries to establish their traditionalist concept of legitimate political power and its distinctions compared to modern concepts. Basing itself to a large extent on the writings of Rabbi Eliezer Menahem Shahk and the “Lithuanian” haredi daily Yated Neeman, the article investigates the haredi understanding of freedom and democracy versus traditional Jewish law (halakhah), focusing on both haredi theoretical explanations of the concepts and on their actual political practice. It especially examines the haredi attitudes as regards three subjects: issues concerning a possible Israeli constitution, basic laws, and the function of the high court as a constitutional court. Hereby the differences between the haredi understanding and use of the term democracy and the modern liberal concept are pointed out. The last part of the article focuses on the electoral basis of haredi power, the growth of haredi communities by natural population increase, new haredi immigrants, new returnees to tradition, and the ability of in particular Shas to enlist voters from traditional (but non-orthodox) economically weak Sephardic circles. The article points to weaknesses in this power base which could in the future create problems for the haredi parties in their attempt to preserve the “status quo”, the balance between secular and religious in Israeli public life.